The impact of motivational factors on employee job satisfaction in the organization / Noor Halina Hamidin and Amirah Su’aidah Haris Fadzilah - Hamidin, Noor Halina; Haris Fadzilah, Amirah Su’aidah (Faculty of Business and Management, 2013)
Job satisfaction had become one of the important elements in one’s organization that can helps in their survival, productivity and also profitability. Employee job satisfaction is a continuous challenge for human resource manager because it is hard to determine their employee job satisfaction. When the individual feels that the organization he or she work does not fulfil his or her needs anymore or they feel unmotivated which can lead to job dissatisfaction, the intention to leave would be triggered in one’s mind. The purpose of this study is to examine the relationship between company policies, relationship with other and quality of supervision with the employee job satisfaction. The data has been collected from employees at Jabatan Tenaga Kerja Melaka and Melaka International Trade Centre by distributing questionnaire to the 65 employees that being selected randomly. Results showed that the significant correlation relationship between the hygiene factors and job satisfaction. This study also used multiple regression analysis in order to identify which factor is most dominant to the job satisfaction in both organizations. This study is said to be beneficial to both of the company in order to increase their employee job satisfactions and reduce turnover. Recommendations for future research are also having been discussed.